Theory of Planned Action and rate of exercise: a predictive model for adolescent students in physical education - Huéscar, Elisa; Rodríguez-Marín, Jesús; Cervelló, Eduardo; Moreno-Murcia, Juan A. (Anales de Psicología / Annals of Psychology, 2014)
This study analyzes some factors that influence the rate of exercise among Spanish adolescent students, using the theorical framework of the Theory of planned behavior (Ajzen, 1991). Participants were 698 physical education students who completed the questionnaires of the theory of planned behavior (TPB) and the Habitual Physical Activity Questionnaire. The results, via of structural equation modeling, showed that the attitudes, norms and control factors of the Theory of planned behavior predicts the future intention to practice physical exercise, and that intention predicts positively the rate of exercise practiced by adolescents. The results provide support for the Theory of planned behavior and highlight the benefits of promoting physical exercesi through support to the motivational antecedents of attitude, regulation and control in adolescence, given its importance in establishing healthy habits in young people.